PENGARUH PENGEMBANGAN KARIR DAN INSENTIF TERHADAP KINERJA KARYAWAN PADA HOTEL RESTY MENARA PEKANBARU - Syarifah Suci Marza; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aims to determine the effect of career development and incentives on employee performance partially and simultaneously. This study used questionnaires and interviews in data collection and was distributed to 44 respondents at Hotel Resty Menara Pekanbaru. The data is processed using descriptive analysis and quantitative analysis through SPSS by testing the validity, reliability, simple linear regression analysis, multiple linear regression, determination (R2), t test (partial) and F test (simultaneous). This study shows the results that the t test with the variable career development and incentives partially has a significant effect on employee performance and for the results of the F test shows that simultaneously career development and incentives have a significant effect on employee performance with an R Square value of 0.752. This shows that career development and incentives have an effect of 75.2% on employee performance while the remaining 24.8% are influenced by other variables not examined in this study.Keywords: Career Development, Incentives, Performance.